Aspectos da argumentação: um enfoque teatral da linguagem - Jesus, Waldivia Maria de (2011)
This thesis is situated in the line of research reading, writing and teaching of Portuguese Language, is theoretically grounded in text linguistics, the cognitive aspects and socio-interactionist, complemented by Learning Theories. With a focus on practices of reading and writing of argumentative texts, with tending opinionated, it has aims to investigate the macro and micro-structural aspects of argumentative discourse, observing their function within intercommunicative processes; see how the linguistc theories and learning theories can support the elected teaching practices of teachers. It has by hypothesis that work with language, with emphasis on the ideia of linguistic activity tends to resize the look on teaching practices requiring innovation strategies and procedures, to the light of the dialogism between scientific knowledge and teachers practices, to promote the teaching of communicative use of language. The analysis material is constituted by reports of our experiences with reading and writing workshops realized with teachers of the Basic Education, Public Education Network, of the city of São Paulo. The hypothesis that guided the research was partially confirmed by the results obtained in reading and writing workshops. The results revealed that the work with language, with emphasis on the ideia of linguistic activity, encourage teachers to resize the look on the practices of language teaching and innovate teaching strategies and procedures, but does not develop skills so that they promote dialogue between scientific knowledge and practices of teaching communicative use of language. The results revealed that the development of skills to promote dialogue between scientific knowledge and practices of teaching is necessary to invest in language training for teachers and deepening of theatrical knowledge